ANALISIS BRAND AWARENESS PRODUK COKLAT SILVERQUEEN DI KALANGAN MAHASISWA UBSI CIKARANG - Ayu azizah; khoirul ulum (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
At this time the Indonesian people already have quite complex needs. Due to the limited time each individual prefers food that is practical and easy to carry everywhere, one of the choices for snacks that is often chosen is chocolate. The aim of this study was to examine the analysis of brand awareness among university students regarding silverqueen brand chocolate products. This type of research conducted descriptive method using primary and secondary data. From the results of the research, information was obtained that the silverqueen chocolate brand is the most widely known, popular and top of mind among students.